Application of Health Technology Assessment for Oncology Care in India: Implications for Ayushman Bharat Pradhan Mantri Jan Aarogya Yojana - Gupta, Nidhi; Jyani, Gaurav; Rajsekar, Kavitha; Gupta, Rakesh; Nagar, Anu; Gedam, Praveen; Prinja, Shankar (Indian Journal of Medical and Paediatric Oncology, 2021)
A health system is considered efficient when it provides maximum health gains to the population from the available resources. Newer drugs, diagnostics and treatment strategies aim to improve the health of the population, however, they come at an increased cost. Therefore, for an efficient health system, it needs to be decided if the extra cost being incurred is justified to achieve the extra health gains. In this regard, health technology assessment (HTA) helps to make evidence informed decisions by evaluating relative cost and benefits of the available interventions. Economic evidence generated by HTA can also be used in framing standard treatment guidelines (STGs) for high-cost cancer care. In multi-payer systems like India, the decisions regarding the clinical management of patients are taken based on the patients' ability to pay, which creates inequities in utilization of healthcare. Ayushman Bharat Pradhan Mantri Jan Aarogya Yojana (AB PM-JAY) offers an opportunity to ensure equity as it reduces financial barriers, besides having a potential to affect efficiency by including only cost-effective interventions in the benefit package. As a result, informed clinical decisions based upon HTA evidence can make cancer treatment more efficient, equitable and affordable for the patients.
Keywords: cost-effectiveness; health economics; health insurance; Health Technology Assessment; medical oncology; priority setting; universal health coverage